Identifikasi jenis serangga hama pada tanaman jagung (Zea mays) di Kota Tarakan - Nurmaisah Nurmaisah; Nunuk Purwati (Jurnal Proteksi Tanaman Tropis, 2021)
This research aimed to identify pest insects that harm maize so the result can be used as a reference to determine the strategy to control them. This research was conducted in North Tarakan District, North Kalimantan Province, from May 2020 until October 2020. The research showed that insects found on maize using insect traps consisted of 6 ordo, 12 families, and 12 species with a total of 190 individuals. Of 190 individuals, those insects' roles act as pollinators by 25%, predator 17%, parasitoid 17%, and 33% as herbivore. The biggest role of the insects in the maize field act as herbivores or pests by 33%. The high pest population is closely related to the preference of hostplant, plant age, and climate. In the study, 4 species of maize pests were found: Locusta migratoria, Atherigona soccata, Cochliomyia macellaria, and Musca domestica. Keywords: diversity, identification, insect, pest, Zea mays